(untitled) (Ameghiniana, 2013)
The reproductive structures of Corystospermaceae from Argentina are descríbed. The following species are analyzed: Pteruchus dubius varo barrealensis (Freng.) n. comb., P. simmorulsi (ShiL) Townrow, Umkomasia macleani Th. and U. speciosa n. sp. Several specimens are attributed to Umkomasia sp. It. is also concluded that U. cacheutensis Fr. is unrelated to Corystospermaceae. Synonymy, tipíficatíon, descriptions, remarks, stratigraphic and geographic distribution and illustrations of the taxa are al so given.